Impaired cognitive performance in drug free users of recreational ecstasy (MDMA). Issue 6 (1st June 2000) - Gouzoulis-Mayfrank, Euphrosyne; Daumann, Jörg; Tuchtenhagen, Frank; Pelz, Susanne; Becker, Steffanie; Kunert, Hans-Jürgen; Fimm, Bruno; Sass, Henning
Abstract : OBJECTIVES: Ecstasy (3, 4-methylenedioxymethamphetamine (MDMA) and related congerers: MDA, MDEA) is the name given to a group of popular recreational drugs. Animal data raise concern about neurotoxic effects of high doses of ecstasy on central serotonergic systems. The threshold dose for neurotoxicity in humans is not clear and serotonin is involved in several functions including cognition. The purpose of this study was to investigate cognitive performance in a group of typical recreational ecstasy users. METHODS: A comprehensive cognitive test battery was administered to 28 abstinent ecstasy users with concomitant use of cannabis only and to two equally sized matched groups of cannabis users and non-users. The sample consisted of ecstasy users with a typical recreational use pattern and did not include very heavy users. RESULTS: Ecstasy users were unimpaired in simple tests of attention (alertness). However, they performed worse than one or both control groups in the more complex tests of attention, in memory and learning tasks, and in tasks reflecting aspects of general intelligence. Heavier ecstasy and heavier cannabis use were associated with poorer performance in the group of ecstasy users. By contrast, the cannabis users did not differ significantly in their performance from the non-users. CONCLUSIONS: The present data raise concern that use of ecstasy possibly in conjunction with cannabis may lead to cognitive decline in otherwise healthy young people. Although the nature of the emerging cognitive disturbance is not yet clear, an impairment of working memory might be the common denominator underlying or contributing to declines of performance in various tasks. The cognitive disturbance is likely to be related to the well recognised neurotoxic potential of ecstasy. The data suggest that even typical recreational doses of ecstasy are sufficient to cause neurotoxicity in humans.